SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-âV* - SLOOTEN, D. F. VAN (REINWARDTIA, 1952)
Some 70 years ago Thiselton Dyer showed Dipterocarpaceae from New Guinea to the Linnean Society of London. This event is referred to in the "Journal of Botany"1"Mr Tbiselton Dyer exhibited the Dipterocarpaceae collected by Beccari on his visit to New Guinea in 1872. These were only three in number, an extremely poor result compared with the extraordinary abundance and variety in the forms belonging to this family previously collected by the same botanist in the adjacent island of Borneo, . . The Dipterocarpaceae being, perhaps, the most characteristic family of the IndoMalayan Flora,the poverty of its representation in New Guinea was a conclusive proof that its vegetation was not a markedly Malayan type."